(untitled) (World Science, 2019)
Chronic heart failure (CHF) is a global public health problem. Despite all the technical advances available in modern cardiology, a medical strategy for the treatment of CHF has been and remains the main focus of therapeutic intervention. А particular problem is the treatment of CHF with concomitant pathology. The modern pharmacological strategy for the treatment of patients with CHF and iron deficiency anemia, except iron preparations, must take into account the use of agents that have antihypoxic, antioxidant and membrane-stabilizing effects, and at the same time regulatory effect on the metabolism of physiologically active compounds to improve the condition of patients. Therefore, this study is aimed to evaluate the effectiveness of iron deficiency anemia’s correction, identify and compare the effect of oral ferrotherapy and combined use of ferrotherapy with L-carnitine on clinical and instrumental parameters of patients with chronic heart failure with reduced ejection fraction of left ventricle as possible variants of additional therapy to standard treatment.